2012
DOI: 10.1111/j.1745-4514.2012.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenol Content, Antioxidant Activities and α-Glucosidase Inhibition of Sesame Cake Extracts

Abstract: Sesame cake, the byproduct obtained after the removal of oil is presently used as cattle field. Present study evaluates the a-glucosidase, a-amylase inhibition and antioxidant properties of black sesame cake extracts. For that purpose, defatted seeds were sequentially extracted with ethyl acetate, methanol, methanol-water 70:30 (v/v) and water. Among the extracts tested, methanol extract demonstrated better antioxidant activities (2,2-diphenyl-1-picrylhydrazyl, hydroxyl and superoxide radical) and total phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…M o r e o v e r b o t h s a m p l e s h a v e s t r o n g e r α-glucosidase inhibition than α -amylase. These results correlates with the work of Reshma et al 32 who reported a stronger α-glucosidase inhibition than α -amylase Previous findings have also revealed a stronger inhibition of α-glucosidase and mild inhibition of α-amylase as a good therapeutic strategy for the management of type-2 diabetes 35 . The inhibition of these enzymes can be attributed to the presence of phenolic monotepernes and sesquiterpenes in the essential oils.…”
Section: Antidiabetic Properties Of Essential Oils From a Me-supporting
confidence: 90%
See 1 more Smart Citation
“…M o r e o v e r b o t h s a m p l e s h a v e s t r o n g e r α-glucosidase inhibition than α -amylase. These results correlates with the work of Reshma et al 32 who reported a stronger α-glucosidase inhibition than α -amylase Previous findings have also revealed a stronger inhibition of α-glucosidase and mild inhibition of α-amylase as a good therapeutic strategy for the management of type-2 diabetes 35 . The inhibition of these enzymes can be attributed to the presence of phenolic monotepernes and sesquiterpenes in the essential oils.…”
Section: Antidiabetic Properties Of Essential Oils From a Me-supporting
confidence: 90%
“…These enzymes are carbohydrate-hydrolyzing enzymes that are commonly used as therapeutic targets to modulate postprandial hyperglycemia. Synthetic inhibitors of these enzymes such as acarbose, voligbose and miglitol reduce postprandial hyperglycemia via inhibition of enzymatic breakdown of complex carbohydrates which can delay absorption of glucose into the bloodstream 32,33 . However these inhibitors are limited in use due to their side effects and failure to alter the course of diabetic complications.…”
Section: Antidiabetic Properties Of Essential Oils From a Me-mentioning
confidence: 99%
“…[65] reported that a wide variation in ash content of sesame varieties exists which is an index of total mineral matter present in the seeds. Iranian [23] sesame varieties Indian [70] sesame cake extracts USA [67] black sesame USA [67] soybean Nigerian [50] Table 4 shows anti-nutritional and antioxidant contents of raw sesame varieties. Results showed significant (p ≤ 0.05) differences in phytic acid contents between varieties.…”
Section: Mineral Composition Of Sesame Seed Varietiesmentioning
confidence: 99%
“…Compounds present in the extract may inhibit this process by competing with deoxyribose for • OH or, at an earlier stage, by interfering with Fenton's chemistry (Aruoma 2003;Reshma et al 2013). Reducing power, proving the electron-donating capacity of compounds, is also considered as an indicator of their potential antioxidant activity (Prior and Cao 1999).…”
Section: Bioactive Potential Of Tempe and Buckwheat Groatsmentioning
confidence: 99%